MHD Flow of a Micropolar Fluid past a Stretched Permeable Surface with Heat Generation or Absorption - Khedr, M.-E. M. M.; Chamkha, A. J. J.; Bayomi, M. (Nonlinear Analysis: Modelling and Control, 2009)
This work considers steady, laminar, MHD flow of a micropolar fluid past a stretched semi-infinite, vertical and permeable surface in the presence of temperature dependent heat generation or absorption, magnetic field and thermal radiation effects. A set of similarity parameters is employed to convert the governing partial differential equations into ordinary differential equations. The obtained self-similar equations are solved numerically by an efficient implicit, iterative, finite-difference method. The obtained results are checked against previously published work for special cases of the problem in order to access the accuarcy of the numerical method and found to be in excellent agreement. A parametric study illustrating the influence of the various physical parameters on the skin friction coefficient, microrotaion coefficient or wall couple stress as well as the wall heat transfer coefficient or Nusselt number is conducted. The obtained results are presented graphically and in tabular form and the physical aspects of the problem are discussed.
Keywords: MHD flow; micropolar fluid; stretched surface; heat generation or absorption